Given: In figure, PR > PQ and PS bisects ∠QPR.
To Prove: ∠PSR > ∠PSQ
Proof: In ∆PQR,
PR > PQ | Given
∴ ∠PQR > ∠PRQ ...(1)
| Angle opposite to longer side is greater
∵ PS is the bisector of ∠QPR
∴ ∠QPS = ∠RPS ...(2)
In ∆PQS,
∠PQR + ∠QPS + ∠PSQ = 180° ...(3)
| ∵ The sum of the three angles of a A is 180°
In ∆PRS.
∠PRS + ∠SPR + ∠PSR = 180° ...(4)
| ∵ The sum of the three angles of a ∆ is 180°
From (3) and (4),
∠PQR + ∠QPS + ∠PSQ
= ∠PRS + ∠SPR + ∠PSR
⇒ ∠PQR + ∠PSQ = ∠PRS + ∠PSR
⇒ ∠PRS + ∠PSR = ∠PQR + ∠PSQ
⇒ ∠PRS + ∠PSR > ∠PRQ + ∠PSQ
| From (1)
⇒ ∠PRQ + ∠PSR > ∠PRS + ∠PSQ
| ∵ ∠PRQ = ∠PRS
⇒ ∠PSR > ∠PSQ.
[Hint. Produce AD to E such that AD = DE and join C and E.]
OR
Prove that the sum of any two sides of a triangle is greater than twice the length of median drawn to the third side.
Prove that the sum of the three sides of a triangle is greater than the sum of its three medians.
OR
Prove that the perimeter of a triangle is greater than the sum of its three medians.